A Covenantal Christology - Cunningham, Philip A. (Studies in Christian-Jewish Relations, 2011)
One of the major theological questions confronting the post-Nostra Aetate Church is how to relate the Christian conviction in the universal saving significance of Jesus Christ with the affirmation of the permanence of Israel’s covenanting with God. The meanings of covenant, salvation, and the Christ-event are all topics that must be considered. This paper proposes that covenant, understood in a theological and relational sense as a human sharing in God’s life, provides a useful Christological and soteriological perspective. Jesus, faithful son of Israel and Son of God, is presented as covenantally unifying in himself the sharing-in-life between God and Israel and also the essential relationality of God. The Triune God’s covenanting with Israel and the Church is seen as drawing humanity into an ever-deepening relationship with God through the Logos and in the Spirit, with both Israel and the Church having distinct duties in this relational process before God and the world.